Effect of Biofertigation and Chemical Fertilizers on Yield Attributes and Yield of Rabi Maize (Zea mays L.) - Kiran, A. Sai; Kumar, K. Avil; Devi, M. Uma; Naik, B. Balaji; Triveni, S. (International Journal of Economic Plants, 2022)
A field experiment was conducted on maize (Zea mays L.) during rabi (November - February), 2018–19 to study the effect of drip fertigation of Nitrogen (N), Potassium(K) and microbial consortium (MC) at Water Technology Centre, College of Agriculture, PJTSAU, Rajendranagar, Hyderabad. The experiment was laid out in randomized block design and replicated thrice. The treatments, comprising of two fertility levels viz., 75% and 100% recommended dose (RD) of N&K as first factor and biofertigation of MC as second factor. The interaction effect between RD of N, K and biofertigation of MC was not significant. Significantly higher cob length, cob girth, number of rows cob-1, cob weight, number of grains cob-1 and grain weight cob-1 were recorded with fertigation of 100% RD of N&Kcompared to 75% RD of N&K and five MC biofertigation recorded significantly higher cob length, cob girth, number of rows cob-1, cob weight , number of grains cob-1 and grain weight cob-1 than that of treatment without application of MC and was on par with biofertigation of MC three times. Maize grain and stover yield recorded with 100% RD of N&K were significantly higher compared to 75% RD of N&K. Biofertigation of MC five times and three times were on par and recorded significantly higher grain and stover yield compared to treatment without application of MC. Significantly lower grain and stover yield were observed under treatment without application of MC